DERECHO DE LOS TRABAJADORES A LA DESCONEXIÓN DIGITAL EN EL ÁMBITO LABORAL ESPAÑOL - Sánchez Trigueros, Carmen (Revista de Derecho, 2022)
After the modification operated by Organic Law 3/2018, of December 5, on the Protection of personal data and guarantee of digital rights, art. 20 bis of the Workers’ Statute expressly recognizes that workers have the right to privacy in the use of digital devices made available to them by the employer, to digital disconnection and privacy from the use of video surveillance and geolocation devices, in the terms established in current legislation on the protection of personal data and guarantee of digital rights. Equivalent rights are particularly recognized for public employees (artículo 14 of Royal Legislative Decree 5/2015, of October 30, which approves the revised text of the Law of the Basic Statute of Public Employees). The scope of these rights extends beyond the performance of the activity in person at the workplace: arts. 17 and 18 of Royal Decree Law 28/2020, of September 22, on remote work regulate the right to privacy and data protection and the right to digital disconnection of people who perform their work remotely, referring to the collective agreements or agreements the terms of its exercise.
Keywords: digital disconnection; new technologies; working hours; hours and rest; family conciliation; health and privacy; fundamental rights